2020
DOI: 10.3390/nu12113235
|View full text |Cite
|
Sign up to set email alerts
|

Animal and Cellular Studies Demonstrate Some of the Beneficial Impacts of Herring Milt Hydrolysates on Obesity-Induced Glucose Intolerance and Inflammation

Abstract: The search for bioactive compounds from enzymatic hydrolysates has increased in the last few decades. Fish by-products have been shown to be rich in these valuable molecules; for instance, herring milt is a complex matrix composed of lipids, nucleotides, minerals, and proteins. However, limited information is available on the potential health benefits of this by-product. In this context, three industrial products containing herring milt hydrolysate (HMH) were tested in both animal and cellular models to measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
17
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 60 publications
9
17
3
Order By: Relevance
“…The discrepancy might be a result of differences in the administration route, dose and composition of the test materials between the two studies. In our study, the entire herring milt was directly dried up or pretreated with enzymatic hydrolysis of proteins prior to dry up, whereas the study by Durand et al used herring milt protein hydrolysate extracts that contained different protein, lipid, nuclei acid, and astaxanthin contents [ 22 ]. The dose of the test materials in the study by Durand et al was 208.8 mg/kg by daily gavage, which was around 60-fold lower than the dose provided through diet in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The discrepancy might be a result of differences in the administration route, dose and composition of the test materials between the two studies. In our study, the entire herring milt was directly dried up or pretreated with enzymatic hydrolysis of proteins prior to dry up, whereas the study by Durand et al used herring milt protein hydrolysate extracts that contained different protein, lipid, nuclei acid, and astaxanthin contents [ 22 ]. The dose of the test materials in the study by Durand et al was 208.8 mg/kg by daily gavage, which was around 60-fold lower than the dose provided through diet in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A mouse study showed that dietary supplementation of herring milt tended to lower the plasma level of several pro-inflammatory cytokines [ 20 ]. Several in vivo and in vitro studies have shown that proteins, protein hydrolysates, or peptides of sardine, salmon, and tuna lower pro-inflammatory cytokine release, inflammatory cell count [ 13 , 45 , 46 , 47 ], and the production of inflammatory mediator iNOS [ 22 ]. The anti-inflammatory benefits of herring milt and fish proteins/hydrolysates may be related at least in part to their high contents of omega-3 EPA and DHA, which are well-established for the anti-inflammatory properties [ 20 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of this Special Issue was to expand and add to the research which uses genomics technologies in the development of personalized nutrition recommendations. This Special Issue on “Genomics and Personalized Nutrition” features five original articles [ 5 , 6 , 7 , 8 , 9 ] and four reviews [ 10 , 11 , 12 , 13 ] which examine two facets of personalized nutrition: 1—genomics and food bioactive compounds; and 2—genetic variations and diet interactions.…”
mentioning
confidence: 99%
“…Two articles in this Special Issue establish the impact of food bioactive compounds on several genomic parameters, such as gene expression and microbiome, to understand the effects on metabolic syndrome. First, Durand et al, 2020 [ 5 ] demonstrate that a supplement of milt herring hydrolysates improves glycemia, reduces inflammation, modulates gene expression in the liver, and alters Lactobacillus abundance. Overall, this study suggests that milt herring is a novel marine ingredient to help fight against metabolic syndrome.…”
mentioning
confidence: 99%